Răspuns :
Salut,
x^4-x^2+1=(x^2)^2+2x^2-3x^2+1=(x^2)^2+2x^2+1-3x^2=(x^2+1)^2-(radical din 3x)^2=(x^2+1- radical din 3x)×(x^2+1+ radical din 3x
[tex]by \\ 7646[/tex]
x^4-x^2+1=(x^2)^2+2x^2-3x^2+1=(x^2)^2+2x^2+1-3x^2=(x^2+1)^2-(radical din 3x)^2=(x^2+1- radical din 3x)×(x^2+1+ radical din 3x
[tex]by \\ 7646[/tex]
![Vezi imaginea Аноним](https://ro-static.z-dn.net/files/d32/e5632a09de6542ac8bd5b824223c06d4.jpg)
Răspuns :
x^4-x^3+1
=(x^2)^2+2x^2-3x^2+1
=(x^2)^2+2
=x^2+1-3x^2
=(x^2+1)^2-radical din 3x)•(x^2+1+radical din 3x)